Impression Motivations and Mental Health in Collegiate Athletes and Musicians: The Benefits of Promoting Virtues - Mary L. Inman; Olufemi A. Oluyedun; Erin Moran; Brendyn Mroz; Madison McCreery (Journal of Clinical Sport Psychology, 2025)
This study identifies two key impression-management motivations that arise in public settings: promoting virtues and preventing harm to one’s image. We explored their impact on mental health—specifically, socially-based perfectionism and depressive symptoms. Drawing from regulatory-focus theory, we predicted promotion motivations would predict strong mental health, prevention motivations would predict poor mental health, and promotion motivations would buffer against the negative effects of prevention motivations. Collegiate athletes and musicians ( N = 262) completed validated measures of impression motivation, perfectionism, and depressive symptoms. Results revealed that athletes reported lower levels of perfectionism and depressive symptoms than did musicians. Across both groups, promotion motivations were generally linked to stronger mental health. For musicians, prevention motivations were associated with higher levels of perfectionism and depressive symptoms. For athletes, promotion motivations mitigated the adverse effects of prevention motivations on perfectionism. Findings suggest that focusing on promoting virtues may provide psychological benefits for both groups.